History supposes Justice - Cohen, Joseph; Zagury-Orly, Raphael (Das Questões, 2020)
This article seeks to firstly demonstrate in which manner the philosophies of history, through the signifiers of crisis and apocalypse, amount to a form of nihilism by persistently surmounting, each in their own manner, the singularity of historical events by integrating and comprehending these in a teleological and eschatological narrative of meaning and truth. In this sense, our attempt is to deploy a novel manner of rethinking our relation to catastrophic historical events where their very singularities engage a historical responsibility which renounces the recourse to the determined logics of crisis and apocalypse in history. Consequently we focus on the spectralityof historical events incessantly returning as occurring singularly to our present, and where each event in history denies its integration in an appeased historical consciousness. This article intends thus to deploy a relation to temporality where the idea of justice provokes a hyperbolical responsibility towards past andfuture deaths and lives in history.